Hepatitis B virus X induces cell proliferation in the hepatocarcinogenesis via up‐regulation of cytoplasmic p21 expression. (17th April 2013) - Yano, Masahiko; Ohkoshi, Shogo; Aoki, Yo‐hei; Takahashi, Hiromichi; Kurita, Sou; Yamazaki, Kazuhide; Suzuki, Kenta; Yamagiwa, Satoshi; Sanpei, Ayumi; Fujimaki, Shun; Wakai, Toshifumi; Kudo, Shin‐ei; et al.
Abstract Background Hepatitis B virus X protein (HBx) has been shown to induce hepatocarcinogenesis by disrupting the functions of intracellular molecules. Cyclin‐dependent kinase inhibitor p21 (Cip1/WAF1), known as a tumour‐suppressor gene, has been reported to have paradoxical function, that is, acting as an oncogene, particularly when expressed in the cytoplasm. The effects of HBx on the expression and function of p21 also remain controversial. Aims We attempted to investigate the role of HBx in the hepatocarcinogenic process, focusing on the association with this paradoxical function of p21. The results obtained were further verified with experiments using the antihepatocarcinogenic action of interferon (IFN)‐β. Methods HBx transgenic mice (Xg) and HBx‐transfected hepatoma cell lines were used. Intracellular localization of p21 was determined by Western blot analysis and immunofluorescence. Results Xg and HBx‐transfected cells exhibited increased expression of p21. Up‐regulation of p21 was positively correlated with the expression of cyclin D1 and inactive phosphorylation of retinoblastoma protein (pRb). These HBx‐induced cell proliferative responses were cancelled by knockdown of p21, which resulted in growth reduction in HBx‐expressing cells, suggesting the oncogenic properties of HBx‐induced p21. HBx induced accumulation of p21 in the cytoplasm, and activation of PKCα was involved. Finally, IFN‐β‐treated Xg liver, as well as hepatoma cells, showed a shift of cytoplasmic p21 to the nucleus, accompanied by the abrogation of HBx‐induced oncogenic modulation. Conclusions Our results suggest that HBx induces hepatocarcinogenesis via PKCα‐mediated overexpression of cytoplasmic p21 and IFN‐β suppressed these molecular events by shifting p21 to the nucleus.